Fysisk aktivitet i barnehagen: Et casestudium av daglig fysisk aktivitet i en avdeling med femåringer - Giske, Rune; Tjensvoll, Magrethe; Dyrstad, Sindre M. (Nordisk barnehageforskning, 2010)
Physical activity in early childhood education and care: A case study of daily physical activity in a group of 5 year old children: Our knowledge of the physical activity level in kindergarten is limited. The intention of the inquiry was to study the variations in the level of activity among 5-year-old children in a section of a day care centre for a week, and find out whether the children reach the recommendations for physical activity. Accelerometer (ActiGraph GT 1M) was used for unbiased measuring of physical activity. In regard to reaching the latest recommendations for physical activity, the results show that the children’s level of activity varies during their stay. It varies both among the children and from one day to the next. During the week seen as a whole, five of ten children meet the recommendation of minimum 60 minutes moderate to high intensity physical activity. The level of activity was a lot higher when the children were playing outside and in a gym as opposed to playing inside.